INFORMATION LITERACY, DISASTER FIQH, AND POLICY ADVOCACY: A STUDY OF NAHDLATUL ULAMA’S VISION IN NATIONAL DISASTER MITIGATION - Putri Alisia Silaen; Junaidi Junaidi; Mardian Idris (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2026)
Indonesia is a country with a highly critical vulnerability to natural disasters due to its geographical location andthe impacts of climate change. The involvement of non-state actors, such as Nahdlatul Ulama (NU), is crucial in driving responsive public policies through the articulation of Fiqh Bencana (Disaster Jurisprudence). This studyaims to analyze how NU’s theological vision on disasters is constructed and transformed into substantial political advocacy strategies, using a case study of the disaster management movement in North Sumatra in late 2025.Employing a qualitative method with in-depth interviews involving key figures from LBM-NU, LPBI-NU, Muslimat NU, GP Ansor, and the beneficiaries, this study finds that NU has successfully bridged